2010
DOI: 10.1186/1756-0500-3-106
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors for typhoid fever after the tsunami, earthquake and under normal conditions in Indonesia

Abstract: BackgroundAlthough typhoid transmitted by food and water is a common problem in daily life, its characteristics and risk factors may differ in disaster-affected areas, which reinforces the need for rapid public health intervention. Surveys were carried out post-tsunami in Banda Aceh, post-earthquake in Yogyakarta, and under normal conditions in Bandung, Indonesia. Logistic regression analysis was used to assess the risk factors with the dependent variable of typhoid fever, with or without complications.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…As in the case of cholera, areas with endemic typhoid fever typically have poor sanitation and lack access to clean drinking water; these regions are particularly susceptible to large outbreaks following natural disasters. Investigators found that following the 2004 Indonesian tsunami, transmission of typhoid fever occurred among internally displaced people as a result of improper food preparation due to the lack of clean water and bacterial contamination of drinking water [28]. The lack of availability of effective antimicrobial drugs also contributed to the spread of disease.…”
Section: Typhoid Fevermentioning
confidence: 98%
See 1 more Smart Citation
“…As in the case of cholera, areas with endemic typhoid fever typically have poor sanitation and lack access to clean drinking water; these regions are particularly susceptible to large outbreaks following natural disasters. Investigators found that following the 2004 Indonesian tsunami, transmission of typhoid fever occurred among internally displaced people as a result of improper food preparation due to the lack of clean water and bacterial contamination of drinking water [28]. The lack of availability of effective antimicrobial drugs also contributed to the spread of disease.…”
Section: Typhoid Fevermentioning
confidence: 98%
“…Typhoid fever can cause serious outbreaks after natural disasters, such as the one that occurred in Puerto Rico after Hurricane Betsy in 1956 and in Indonesia after the tsunami in 2004 [28]. As in the case of cholera, areas with endemic typhoid fever typically have poor sanitation and lack access to clean drinking water; these regions are particularly susceptible to large outbreaks following natural disasters.…”
Section: Typhoid Fevermentioning
confidence: 99%
“…After the tsunami in Aceh, Indonesia, clean water and drug availability were significant independent risk factors, while for the earthquake in Yogyakarta, Indonesia, contact with other typhoid patients and educational level was a significant risk. Although typhoid fever transmitted by food and water is a common problem in daily life, its characteristics and risk factors may differ in disaster-affected areas (Sutiono et al, 2010). A study on risk factors for clinical typhoid fever in South Sulawesi/Indonesia showed that limited education was highly associated with the occurence of typhoid fever.…”
Section: Epidemiologymentioning
confidence: 99%
“…There are histories of outbreaks of typhoid fever following a cyclone in Mauritius in 1980, a complex disaster in Tajikistan in 1992-1997 and following a natural disaster in Calamba, the Philippines, in 2008 [4][5][6]. An investigation of enteric fever in Indonesia also found an association of enteric fever with flooding [7].…”
Section: Introductionmentioning
confidence: 99%